Sistem Pendukung Keputusan Penentuan Keluarga Miskin Di Kelurahan Pilangsari Kecamatan Gesi Dengan Menggunakan Metode Technique For Order Performance By Similarity To Ideal Solution (Topsis) - Fauzan, Arif Nor; , Prof. Dr. Budi Murtiyasa M.Kom (2017)
Village of Pilangsari is one area in Indonesia that far in the collection of poor people still use manual, which is filling the form in paper form that takes a long time. A program created by the researchers is based website, using the Research Technique for Order Performance by Similarity to Ideal Solution is often referred to TOPSIS, TOPSIS is a method of settlement of multi-criteria where this method provides a method of decision-making where alternative chosen is the best alternative that has a distance The closest ideal solution both positive and negative ideal furthest from. Decision support systems can assist the determination of poor people in the village activities especially in terms of citizens' data because in the quest to interpretation percentage reaches 100% it is the highest presentation. Furthermore, to the activities of inputting and accessing get a percentage of 93.3% interpretation. For sorting activities of the poorest and the richest get a percentage of 86.6% in the recapitulation interpretation admin questionnaire.